Review of PRGF Program Design : Overview. (Policy Papers; Policy Paper, 2005)
Part of the Fund's periodic reviews of its policy advice to member countries, and responds to calls by Executive Directors for further staff analysis on improving the design of such programs. In the context of the recent discussions on the design of the broad range of Fund-supported programs, Directors also requested more in-depth analytical studies of disaggregated and homogenous groups, as well as a closer look at how progress towards external viability in low-income countries (LICs) can be improved. The review also seeks to address these requests.